Rancang Bangun Dropping Kontrol Tetesan Infus dengan Sistem Telemetri berbasis Android - Dewi Amane Maulida; Felix Dionisius; Rachmatullah (Journal of Applied Mechanical Technology, 2022)
The infusion system is relatively simple and easy, namely by hanging the infusion bottle on a pole and utilizing gravity so that the infusion drops will flow through the hose and enter until they flow into the veins. In the world of medicine, the use of infusion systems can also be done to enter drugs. The use of this drug must be monitored to ensure the number of doses that have been entered is according to the doctor's prescription with an infusion system. This paper aims to design and manufacture an infusion drip controller with an Android-based telemetry system. The method of this paper begins with designing and using the VDI 2221 method. The main components designed in this paper are the open and closed components of the infusion drop rate. For manufacturing using 3D printing with PLA material. Meanwhile, the measurement results were tested using a measuring cup with a 5 mm scale with ± 0.02 mm of tolerance. The results of this design show that the open and closed tool components are elliptical with an axis in the middle. While the results of the test show a comparison between the required volume and the removal of the tool by 1.2%. The tool can also provide notifications to communication devices when the volume has been reached. So that the tool can be used by following the tolerance rules for infusion and drug intake.